ADMINISTRATIVE LIABILITY OF LEGAL ENTITIES: HISTORY AND PRESENT - Borodin, Ivan; Myronets, Oksana (Proceedings of National Aviation University (archive), 2016)
Purpose: Legal entities are capable to accumulate much more financial, material, intellectual resources to achieve their goals than a natural person. It is important to develop theoretical fundamentals that are necessary for understanding of administrative liability of legal entities and make propositions to improve current legislation about administrative liability of legal entities, a mechanism of its implementation and systematization of legislation in this area. Methods: General scientific, philosophical and specially-legal methods of scientific research have been used. Theoretical and legal framework of an institute of administrative liability of legal entities, preconditions of legislative regulation of administrative liability of legal entities have been investigated with the help of general scientific and philosophical methods. A system analysis method has been used for the analysis of modern administrative legislation, scientific works to determine a concept of “administrative liability of legal entities.” A dogmatic method was valuable to formulate the conclusions and recommendations of practical character within the research issues. Results: It is shown that the legislation about administrative liability of legal entities is in the forming stage, and there are two possible ways of its systematization. It was stressed that both of them are connected with a necessity to bring contradictions about regulation of legal liability of legal entities into line with constitutional norms. It was concluded that a legal entity should be recognized as a subject of administrative liability. Discussion: Administrative liability of legal entities is intended to withstand offences, protect legal rights and interests of citizens, the state, legal entities, established administrative order, and also provide renewal of broken rights and compensation for losses resulting from an offence, give onerous consequences of organizational and material character for offenders. The development of a concept of “administrative liability of legal entities” and its implementation is an important topic for the future research